Recognition of the Pavilion in Relation to the Persian Garden from the Perspective of Fractal Geometry (Case Study: Pavilions of the Fathabad Garden in Kerman) - Mohammadali Ashraf Ganjouei; Mohammad Iranmanesh (منظر)
Despite numerous studies conducted on Iranian gardens, the analytical investigation of the role of gardens in the shaping of pavilions has not received significant attention. In this study, utilizing fractal geometry, we can observe and analyze architectural qualities with mathematical precision and greater detail. This approach aids in re-examining the visual perceptions of the pavilion structure and identifying the missing geometrical value of the garden. This article delves into the relationship between a pavilion and a garden through fractal geometry. The findings are discussed and explored to uncover the architectural complexities of pavilions, which are influenced by the garden and its natural surroundings. A historical garden named Fathabad in the city of Kerman was selected as the case of our study. Fractal dimension analysis is employed to analyze the two pavilions’ facades. The box-counting method was applied to measure the fractal dimensions of the facades at three scales. The results would reveal the relationship between each of the two pavilion facades and the garden. The findings indicate that while different facades share similar architectural elements, they exhibit diverse fractal dimensions. These dimensions reveal the position of each facade relative to the garden’s geometry, and the variable fractal dimension within each level signifies distinct relationships between the levels and the garden axes. Additionally, facades parallel to the main garden pond or those without a direct view exhibit a lower fractal dimension. Although facade openness can serve as a measure of its connection to nature, fractal analysis demonstrates that facades with multiple openings have varied relationships with the garden. Furthermore, the analysis of decorative elements reveals that in parts of the facade with fewer openings, ornamentation may be influenced by the garden’s natural features. In summary, fractal geometry elucidates how the garden and its elements impact different parts of the facades of the two pavilions.